2021
DOI: 10.24034/j25485024.y2021.v5.i2.4490
|View full text |Cite
|
Sign up to set email alerts
|

Opini Going Concern: Ditinjau Dari Agensi Teori Dan Pemicunya

Abstract: Kontinuitas perusahaan dapat diidentifikasi dari laporan keuangannya yang dikeluarkan oleh auditor. Kemampuan perusahaan dalam menyelesaikan kewajibannya merupakan hal yang diperhatikan oleh perusahaan untuk mempertahankan eksistensinya dalam persaingan yang ketat ini. Oleh karena itu, penelitian ini memiliki tujuan untuk mengetahui pengaruh pada ukuran perusahaan, perkembangan perusahaan, rasio hutang terhadap ekuitas, kualitas audit, opini audit tahun sebelumnya pada kecenderungan penerimaan opini audit goin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
21

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 15 publications
0
7
0
21
Order By: Relevance
“…According to Masfiah (2021), states that a company with positive sales growth has a tendency to maintain its business continuity, whereas a company with negative sales growth has a greater tendency towards bankruptcy. The previous research done by Akbar & Ridwan (2019), Endiana & Suryandari (2021), dan Al'adawiah et al (2020) showed that company growth has negative effect on going concern opinion acceptance. Meanwhile, Kurnia (2018), Masfiah (2021), Febrianti & Suhartini (2022) dan Halim (2021) found that company growth has no effect on going concern opinion acceptance.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…According to Masfiah (2021), states that a company with positive sales growth has a tendency to maintain its business continuity, whereas a company with negative sales growth has a greater tendency towards bankruptcy. The previous research done by Akbar & Ridwan (2019), Endiana & Suryandari (2021), dan Al'adawiah et al (2020) showed that company growth has negative effect on going concern opinion acceptance. Meanwhile, Kurnia (2018), Masfiah (2021), Febrianti & Suhartini (2022) dan Halim (2021) found that company growth has no effect on going concern opinion acceptance.…”
Section: Introductionmentioning
confidence: 90%
“…The second factor that can influence the acceptance of going concern opinions is company growth. Company growth is the condition of a company experiencing development both in terms of assets and in terms of sales growth (Endiana & Suryandari, 2021). According to Masfiah (2021), states that a company with positive sales growth has a tendency to maintain its business continuity, whereas a company with negative sales growth has a greater tendency towards bankruptcy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [14], signal theory states that external parties will react positively or negatively depending on the information they receive. If the information received is good, they will react positively to the company, and vice versa [15].…”
Section: Signaling Theorymentioning
confidence: 99%
“…Melalui penerbitan laporan keuangan, manajer harus memberi informasi kepada pihak pemangku kepentingan karena sinyal disampaikan kepada stakeholders berbentuk informasi penting terkait status perusahaan (Rochman and Andayani 2023). Melalui laporan keuangan, manajer memberi informasi laba, tetapi manajer harus bisa mengimplementasikan aturan-aturan akuntansi secara benar dan valid agar laba berkualitas tinggi mampu diperoleh tanpa melebihlebihkan, sehingga para pengguna laporan keuangan bisa mengambil keputusan melalui informasi yang didapatkan (Endiana and Suryandari 2021).…”
Section: Signaling Theoryunclassified